Geochemical controls on arsenic release into groundwaters from sediments: in relation to the natural reactive barrier - Berube, Michelle M. (Kansas State University, 2017)
Elevated levels of dissolved arsenic (As), iron (Fe) and manganese (Mn) are seen in the shallow, anoxic groundwaters of southeast Bangladesh on the Ganges- Brahmaputra- Meghna River delta. Over the past decade the mechanisms of As release have been widely debated. It is understood that As can sorb onto Fe-bearing minerals and can be subsequently released when reactions, such as microbially driven processes, occur. This study takes a multi disciplinary approach to understand the extent of the natural reactive barrier along the Meghna River and to evaluate the role of the natural reactive barrier in As sequestration and release in groundwater aquifers. River water and groundwater interactions occur in the hyporheic zone, which is defined as the transient subsurface region where river water and groundwater mix. The natural reactive barrier can develop within the hyporheic zone, where Fe-bearing minerals accumulate with a potential for As sorption, along with reworking and re-deposition of sediments along the riverbank. Shallow sediment cores, and groundwater and river water samples were collected from the east and west banks of the Meghna River in Jan. 2016. Groundwater and river water samples were tested for total dissolved Fe, Mn, and As concentrations; δ₂H, δ₁₈O isotopic ratios. Fluorescence spectroscopic characterization of groundwater organic matter provided insight into the hydro-geochemical reactions active in the groundwater and the hyporheic zone. Eight sediment cores of ~1.5 m depth were collected ~10 m away from the edge of the river. Vertical solid-phase concentration profiles of Fe, Mn, and As were measured by four different methods (hand-held XRF, and ICP-OES analysis of 3 digestions: aquaregia (HNO₃: HCl 1:3), 1.2 M HCl, and 1 M NaH₂PO₄ + 1 M L-ascorbic acid extractions). Enrichment of solid phase Fe, Mn, and As and the presence of possible Fe and Mn oxides in the sediments illustrate the existence of an natural reactive barrier at this reach of the Meghna. HCl extractions of sediment revealed solid-phase As accumulation along the west riverbank reaching concentrations of ~1500 mg/kg. Aqueous geochemical results showed the highest dissolved As concentrations in shallow wells (<30 m depth), where organic matter was fresh, humic-like, and aromatic. Humic-like dissolved organic matter present in the groundwater may enhance Fe oxide dissolution. Microbial reduction of organic matter prompts the reduction of Fe³⁺ to Fe²⁺, causing As to mobilize into groundwater. This study quantified the extent of As accumulation in the sediments along a 1 km stretch of the Meghna River. These findings contribute to the understanding of geochemical processes involved in As release into groundwaters from sediments within a fluvial deltaic environment.
Keywords: Arsenic; Natural reactive barrier; Sediment geochemistry; Dissolved organic matter; Groundwater